THE CLASSROOM-BASED ASSESSMENT FOR READING COMPREHENSION : A Case Study at an MAN in Makassar - Kaharuddin, - (2009)
One of the purposes of teaching English reading as a foreign language skill to the students is to encorage them to construct meanings of what they read. Assessment, as a part of teaching and learning processes, should support this purpose. The English teachers should motivate students in reading through an appropriate assessment.The objective of this study is to investigate how the English teachers carry out reading assessment through the classroom-based assessment. Specifically, the aims of this study include (1) to identify teachers' understanding of the classroom-based reading assessment in terms of purpose, the timing (when to assess), and the assessed reading comprehension skills, (2) to identify the techniques employed by the teachers, and (3) to identify how the teachers construct the classroom-based reading assessment in terms of using different material sources in designing reading assessment and methods to provide feedback of the assessment. This research was conducted at one of Madrasah Aliyah Negeri in Makassar. The respondents are three English teachers of the school and the data were obtained by using questionnaire, interview, observation, and document study. Questionnaire was carried out to answer research question 1, 2, and 3. Interview was carried out to complete the questions for research question 1 and 2 that were not covered on questionnaire. Observation and document study were carried out to clarify the data obtained from the questionnaire and interview. The finding of this study reveals that respondents are well-informed of the purpose of classroom-based reading assessment. The timing (when the respondents assessed students' reading comprehension) was periodical. They tended to assess reading skills which were related to literal and interpretive level of comprehension. The techniques employed by the respondents in assessing reading comprehension comprise teacher-conducted and student-conducted methods. Nevertheless, respondents relied on the textbooks in assessing students' reading comprehension. Therefore, they had hardly ever designed reading assessment instruments; instead, the used tasks or exercises provided on the textbooks.